Speech Intelligibility in Children with Cochlear Implant, with Hearing Aids and Normal Hearing - Mohammad A'shouri; Seyyedeh Somayyeh Jalil-Abkenar; Saeed Hassan-Zadeh; Ma'soumeh Pourmohammadreza-Tajrishi (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The purpose of the present research was to compare speech intelligibility in children with cochlear implant, with hearing aids and normal hearing in Tehran province.  Materials & Methods: Sixty children underwent this analytic and comparative research. They were divided into three groups and each group contains 20 children. First and second group were selected, ordinarily, from children with cochlear implant and hearing aids by the in available method while that third group were selected from children with normal hearing randomly. The instruments of this research were Riven intelligence test and Speech Intelligibility Rating (SIR). The obtained data were statistically analyzed by one-way ANOVA and Post-Hoc Scheffe. Results: The findings of the research showed that mean scores of speech intelligibility in normal hearing children was significantly more than children of the two groups (P0.05). Conclusion: Speech intelligibility in children with normal hearing was better than children with cochlear implant or hearing aids. Since, speech intelligibility is multidimensional and complex phenomenon, requires specific rehabilitation program in order to achieve more development in speech skill of children with cochlear implant or hearing aids.